The Effect of Drill Exercise Methods and Eye Coordination on Forearm Passing Skills of Volleyball - Prasticia, Atika; Soegiyanto, Soegiyanto; Rahayu, Setya (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
Volleyball is a sport game, which is popular with the general public as well as the beginners (students). Badegan State 1 Junior High School (SMP Negeri 1 Badegan) is one of the schools that conduct volleyball extracurricular activities however the passing ability of the female students who take part in volleyball extracurricular activities, were still low. Therefore, training methods were needed to improve students' forearm passing ability. The method of the research is an experimental research which used factorial plan 2x2. The population of this research is all of the female students on SMP Negeri 1 Badegan, Ponorogo Regency, who followed volleyball extracurricular totally 30 people. To get the sample of this research, used saturated sampling in order to the entire population can be the sample of this research. This research showed that the t-test got 10.405 points and t–table on dk (0.05) (19) in the amount of 1.729. Because of the t–test point is greater than the t-table (-10.405>1.729), it can be concluded that there is an effect of the patterned drill practice method and hand-eye coordination on the forearm passing ability of the female volleyball extracurricular participants at the (State Senior High School of 1 Badegan) SMA Negeri 1 Badegan